Studying the effect of substituting wheat flour with pomegranate peel powder on quality characteristics of biscuit (Damascus University Journal of agriculture sciences, 2023)
This research was aimed to replace wheat flour partially, with pomegranate peel powder at different proportions (0, 2, 4 and 6%), and study the effect of pomegranate peel powder on (color, moisture, ash, total phenolic content, antioxidant activity indices) and organoleptic properties of biscuits.Pomegranate peel powder sample showed a significant increase in the content of total sugars (25.86 g / 100 g dry weight), ash (3.93%), and a significant decrease in the percentage of moisture (7.52%) and proteins (0.70%). Also, these samples showed a significant increase in their total phenols content (206 mg / 100 g dry weight) and antioxidant activity (63.85%). Biscuit samples fortified with pomegranate peel powder with 6% showed a significant increase in total sugars (50.10 g / 100 g dry weight), ash (2.10%), total phenols content (136.65 mg/100g dry weight) and antioxidant activity (72.89%), compared with other biscuit samples. Also, this proportion improved taste, aroma, texture and general acceptability compared with control biscuit samples. Substitution proportion 2% of pomegranate peel powder had the greatest significant effect on reducing moisture content of biscuit samples, reached (6.34%) compared to of control biscuit sample (7.82%). High substitution proportion of pomegranate peel powder led to a significant increase in the content of total phenols by (134.83% to 191.99%) and a significant increase in antioxidant activity, at a rate ranging from (60.52% to 173.30%) compared with control samples.
Keywords: Peel Powder; Biscuit; Chemical Properties; Organoleptic Properties; Color